Measurement on strain rate sensitivity and dynamic mechanical properties of various polymeric materials - Mohd Firdaus, Omar; Hazizan, Md Akil; Zainal Ariffin, Ahmad (Trans Tech Publications, 2011)
Link to publisher's homepage at http://www.ttp.net/